Systematic evaluation of a few proline derivatives as catalysts for a direct aldol reaction - Sutar, Revannath L.; Joshi, Navalkishore N. (Tetrahedron-Asymmetry, 2013)
A series of pyrrolidine derivatives were prepared and examined as catalysts for an aldol reaction. Structural variations in these molecules involved altering the sterics at the alpha-position, the position of the carbonyl group, and the acidities of the hydrogen bonding sites. The effect of these factors on catalytic activity and enantioselectivity was studied. The experimental results revealed that additional sterics at the alpha-position were detrimental. However, no correlation was found between the catalytic activity and N-H acidity. (C) 2012 Elsevier Ltd. All rights reserved.